The Application of Rainwater as Architectural Design Elements For Green Technology Solution In Low Rise Office Building (International Journal of Built Environment and Sustainability, 2018)
Performance of workers in terms of productivity level is determined by many related factors including a comfortable work space. Nevertheless, the discussion on the condition of work space environment namely in low rise office buildings and its related issues on thermal comfort in Malaysia are fairly new and is not well addressed. Past studies indicate that low rise offices found in many well-developed countries tend to utilize air conditioning as easiest ways to create a comfortable work space and to cool down the building interior. This factor had indirectly contributed to the increment of energy consumption namely in urban areas due to the rise of air condition consumption from 40% to 60% annually. As a result, contributed to the formation of urban heat island (UHI) which affect community’s environment and quality of life involving health and comfort. The objective of this paper therefore is to discuss and propose approaches on how to apply rainwater elements in architectural design for achieving thermal benefits through passive cooling. This is vital as Malaysia receives large amount of rainfall throughout the year in which this nature resources may provide advantages as sustainable source in cooling down the building temperature. For this purpose, case study as research strategy is adopted using mixed methodology combining qualitative and quantitative method. To conduct the data analysis, ECOTECT simulation and small field experiments are performed to investigate the cooling effect in low rise office building. Findings indicate that low rise office building which integrates rainwater elements in architectural design potentially improve the building thermal performance thus reducing building’s energy demand for space conditioning. This study is important as by adopting appropriate methods in addressing ecology issues will not only provide a comfortable living environment to the users but also established referential guideline in low rise office design.
Keywords: Passive cooling agent; Thermal comfort; Low rise office; Rainwater design elements